2005
DOI: 10.1101/gad.1348905
|View full text |Cite
|
Sign up to set email alerts
|

A histone code in meiosis: the histone kinase, NHK-1, is required for proper chromosomal architecture in Drosophila oocytes

Abstract: To promote faithful propagation of the genetic material during sexual reproduction, meiotic chromosomes undergo specialized morphological changes that ensure accurate segregation of homologous chromosomes. The molecular mechanisms that establish the meiotic chromosomal structures are largely unknown. We describe a mutation in a recently identified Histone H2A kinase, nhk-1, in Drosophila that leads to female sterility due to defects in the formation of the meiotic chromosomal structures. The metaphase I arrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 64 publications
9
116
0
4
Order By: Relevance
“…Inhibition of Ser10 phosphorylation by inactivating aurora B with hesperadin, an inhibitor, also leads to improper attachment of kinetochore fibers to the chromosome (24), changes in binding properties of chromatin proteins such as HP1 (7,17), and failure to recruit the condensin complex and mitotic spindle assembly (10). NHK-1, a Drosophila homolog of VRK1, phosphorylates T119 in histone H2A and plays an essential role in mitotic progression and in the formation of chromosome architecture in meiosis (1,4,19). Although the net level of phosphorylation of histone H2A by VRK1 was weaker than that seen with H3 during in vitro kinase assay (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Inhibition of Ser10 phosphorylation by inactivating aurora B with hesperadin, an inhibitor, also leads to improper attachment of kinetochore fibers to the chromosome (24), changes in binding properties of chromatin proteins such as HP1 (7,17), and failure to recruit the condensin complex and mitotic spindle assembly (10). NHK-1, a Drosophila homolog of VRK1, phosphorylates T119 in histone H2A and plays an essential role in mitotic progression and in the formation of chromosome architecture in meiosis (1,4,19). Although the net level of phosphorylation of histone H2A by VRK1 was weaker than that seen with H3 during in vitro kinase assay (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…NHK1 phosphorylated H2A at Thr119 in chromatin but not with free histone as the substrate (1). Recent studies showed that NHK1 participates in mitotic progression (4) and maintenance of proper chromosomal architecture (19). These data strongly indicate that NHK1 is a bona fide mitotic histone kinase.…”
mentioning
confidence: 97%
“…Later the unique Drosophila melanogaster ortholog of this human kinase family, the NHK-1 (nucleosomal histone kinase), has also been shown to phosphorylate histones and is essential for chromosome condensation and mitotic progression (47)(48)(49)(50). Histone H3 plays an important role in chromatin condensation once the DNA synthesis has 3 H]GDP followed by incubation with the specified amounts of RCC1 for 5 min and 2 mM GTP without VRK1 or with different amounts of VRK1.…”
Section: Discussionmentioning
confidence: 99%
“…Other less-well-understood candidates that may indeed be the phosphorylation relevant to condensation include H2ASer1ph, H2BSer10ph, H2ATur119ph and H4ph. [85][86][87][88] Histone modifications and chromosome segregation. Histone acetylation has been reported to be associated with chromosome segregation in oocyte meiosis.…”
Section: Functions Of Histone Modifications During Mammalian Oocyte Mmentioning
confidence: 99%